Diagnostic value of the appendicitis inflammatory response (AIR) score. A systematic review and meta-analysis - Roland E. Andersson; Joachim Stark (World Journal of Emergency Surgery)
Abstract Background Clinical scoring algorithms are cost efficient in patients with suspicion of acute appendicitis. This is a systematic review and meta-analysis of the diagnostic properties of the Appendicitis Inflammatory Response (AIR) score compared with the Alvarado score. Methods The PubMed, EMBASE, Web of Science and Google Scholar databases were searched for reports on the diagnostic properties of the AIR score from 2008 to July 18, 2024. A meta-analysis of the receiver operating characteristic (ROC) area and the sensitivity and specificity for all and advanced appendicitis patients was performed. Advanced appendicitis was defined as perforated or gangrenous appendicitis or appendicitis abscess or phlegmon or if described as complicated appendicitis. The risk of bias was estimated via the QUADAS-2 tool. The ROC areas of the AIR score and the Alvarado score were compared. Results A total of 26 reports with a total of 15.699 patients were included. The area under the ROC curve for the AIR score was 0.86 (95% CI 0.83–0.88) for all patients with appendicitis and 0.93 (CI 0.91–0.96) for those with advanced appendicitis, which was greater than the corresponding areas for the Alvarado score (0.79, CI 0.76; 0.81) and 0.88, CI 0.82; 0.95), respectively. At > 4 points, the sensitivity was 0.91 (CI 0.88; 0.94) for all patients with appendicitis and 0.95 (CI 0.94; 0.97) for those with advanced appendicitis. At > 3 points, the sensitivity was 0.95 (0.90; 0.97) for all patients with appendicitis and 0.99 (0.97; 0.99) for those with advanced appendicitis. At > 8 points, the specificity was 0.98 (0.97; 0.99) for all patients with appendicitis and 0.99 (0.97; 0.99) for those with advanced appendicitis. The included studies had a low risk for bias and low heterogeneity. Conclusion The AIR score has a better diagnostic capacity than the Alvarado score does. The AIR score is a safe and efficient basis for risk-stratified management of patients suspected of having appendicitis.